Spelling errors reveal underlying sequential and spatial processing deficits in adults with dyslexia. - Peter, Beate; Albert, Andria; Gray, Shelley (Clinical Linguistics & Phonetics, 2021)
Recent studies showed that some adults with dyslexia have difficulty processing sequentially arranged information. In a companion study, this deficit manifested as low accuracy during a word pair comparison task involving same/different decisions when two words differed in their letter sequences. This sequential deficit was associated with left/right spatial letter confusion. In the present study, we found the same underlying difficulty with sequential and spatial letter processing during word spelling. Participants were the same 22 adults with dyslexia and 20 age- and gender-matched controls as in the companion study. In the spelling task, sequential error rates were higher in the dyslexia group, compared to the controls. Measures of accuracy of serial letter order during the spelling task and the word comparison task were correlated. Only three participants, each with dyslexia, produced left/right letter reversals during spelling. These were the same participants who produced left/right errors when naming single letters. They also had profound difficulty with sequential and left/right letter processing in the spelling and word comparison tasks, and they had the most severe spelling impairment. We conclude that this pervasive, persistent difficulty with sequential and spatial reversals contributes to a severe dyslexia subtype. In the dyslexia group as a whole, additional and separate sources of errors were underspecified word representations in long-term memory and homophone errors that likely represent language-based deficits in word knowledge. In the participants, these three factors (sequential/spatial letter confusion, underspecified word form representation, language-based deficits) occurred either as single factors or in combination with each other.